O futebol e o espírito do tempo: narrativas midiáticas sobre a seleção brasileira e a cultura empreendedora - Casaqui, Vander (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
This essay deals with the media narratives that articulate the image of the Brazil national football team, participant of the 2018 World Cup, with the precepts and prescriptions of the entrepreneurial culture. In this sense, the national tema is considered as an allegory of the nation at a certain historical moment, especially at the moment when the World Cup is held, every four years. The theoretical framework is based on the thesis on the new spirit of capitalism by Boltanski and Chiapello. We discuss football as an object and as a way of understanding Brazil, and we also deal with the narrative elements that construct the Brazilian national team in the media scene. One and other purpose insert the text into the concerns of the research group “Comprehension as a method”.